Falsification of Financial Reports - a Companion of the Market Economy and the Processes of Globalization - Lakis, Vaclovas (Ekonomika, 2008)
In the market economy, the company’s financial reports are the main source of information about its assets, capital, debts, profit, and the flow of its money. It is on the base of financial reports that consumers make various decisions about purchasing shares, giving credits, partnership, etc.The order of managing and preparing financial reports is strictly regulated by countries’ laws, standards, and international standards of accounting and accountability. In the EU, the preparation of financial reports and their consolidation is regulated by the directives and other normative acts whose requirements are included in the local laws of every member state.Financial accounting is handled under certain principles and rules. The following of these principles allows a company to submit correct information about its assets, capital, obligations, income, and expenditures. However. the principles and rules show certain common provisions that can be differently interpreted depending on the situation. Sometimes the standards allow choosing from a number of possible variants. When making use of the possibility, companies often choose a wrong version, thus distorting the real situation in their financial reports. Sometimes they fail to adhere to the rules and principles.The research has shown that the falsification of financial reports is a worldwide phenomenon which transcends the boundaries of separate countries. This pathology of market economy is dangerous as it distorts the market. If it isn’t stopped, participants of the market as the main users of financial reports may cease to consider them reliable, which would have a very harmful effect on the market economy.The wish to falsify financial reports is a result of either extreme pressure from the outside or the company’s inner problems. Shareholders and potential investors do not wish to accept the fact that the value of the shares may reduce due to a natural price fluctuation. Any publicized information about even a minor problem within the company may be disastrous for the company. Therefore, the optimistic note in financial reports is one of the weapons in the competitive battle.The falsification of financial reports may result from the company’s inner problems connected with the situation’s misinterpretation, wrong management solutions, and the absence of the sources of financing.In conclusion, financial reports are forged in order to show that the situation of a company is either better or worse than it really is. The means of the falsification depend on its scale. They can be moderate, active, or aggressive.